Performance of polypropelene and polyester fibres-reinforced reactive powder concretes at elevated temperatures. (10th April 2023) - Hiremath, Parameshwar; Yaragal, Subhash C.
Highlights: Performance of RPC with PP and PE fibres at elevated temperatures is evaluated. Combined effect of PP and PE fibre based RPC, possess good spalling resistance with 0.1% fibre content. Microstructure examination of all RPC mixes is performed, to investigate formation of pores, cracks and evaporation of fibres. Abstract: Reactive Powder Concrete (RPC) is an emerging class of special concrete that falls under the category of ultra-high-performance concrete. RPC offers very superior mechanical properties as compared to conventional concretes. The application of RPC is limited to some of the restricted applications such as, construction of nuclear power plants, precast bridges and girders. The generalized application of RPC is restricted due to the unknown behavior of RPC, when it is exposed to fire load. The dense and fine microstructure of RPC is prone to spalling under elevated temperatures. To combat spalling, RPC is produced with suitable fibres. In this study RPC is prepared with addition of polypropelene and polyester fibres with different fibre dosages like 0.1, 0.5 and 0.9% by weight of cement. The residual mechanical and durability properties of fibre-based RPC are evaluated at elevated temperatures ranging from 200 to 800 °C. Results indicate that the combined effect of polypropelene and polyester fibre-based RPC, possess good spalling resistance with 0.1% fibre content. Fibre dosage of 0.5% has shown superior residual mechanical and durability properties of RPC at elevated temperatures. Formation of pores, cracks and evaporation of fibres due to elevated temperatures is also investigated based on microstructure examination for all RPC mixes.